Electrochemical and Microscopic Studies of the Mild Steel (MS) Surface by using Metronidazole Drug as A Green Inhibitor in 1M HCl Medium (London Journal of Research In Science: Natural and Formal, 2025)
In this paper using the metronidazole pharmaceutical drug compound as a green corrosion inhibitor that can be decreasing the rate of corrosion on metallic surface, as a result of the adsorption of metronidazole on the metal surface. In this regard, we simultaneously present an overview of metronidazole compound performance, as a corrosion inhibitor in 1M HCl, and with presence different concentrations of the drug. By using Electrochemical techniques (open-circuit potential, Potentio-dynamic polarization (PP), Electrochemical Impedance Spectroscopy (EIS), Electrochemical Frequency Modulation (EFM)) that illustrate the nature of adsorption. The surface examination by scanning electron microscopy (SEM), energy dispersive X-ray (EDX), atomic force microscopy (AFM), and Fourier transforms infrared (FT-IR) are confirmed the formation thin film that adsorbed on the metal surface according to the mechanism of the adsorption processes on the polarized metal surface.
Keywords: urban flora; urban ecosystem; species occurrence frequency; Shannon index; biodiversity complexity; biodiversity potential.; density; electron; Radius; Electron Neutrino; Proton; Neutron; Up Quark; Down Quark; Table of Nuclear radiuses and densities.; decoupling; CO2/GDP; U.S. county data; SDG indicator 9.4.1; Graft copolymerization; Cassava starch; Acrylamide; Water Based mudRheological properties; FT-IR; Electrochemical Techniques OCP; PP; EIS; EFM and Surfaces Analysis SEM; EDX; AFM